2020
DOI: 10.5935/0103-507x.20200047
|View full text |Cite
|
Sign up to set email alerts
|

Modified Early Warning Score as a predictor of intensive care unit readmission within 48 hours: a retrospective observational study

Abstract: Objective To evaluate the hypothesis that the Modified Early Warning Score (MEWS) at the time of intensive care unit discharge is associated with readmission and to identify the MEWS that most reliably predicts intensive care unit readmission within 48 hours of discharge. Methods This was a retrospective observational study of the MEWSs of discharged patients from the intensive care unit. We compared the demographics, severity scores, critical illness characteristics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
(38 reference statements)
2
12
0
3
Order By: Relevance
“…It has been proven to be a crucial tool for early identification of patients with high risk of poor outcome. 24 , 39 , 40 In elderly COVID-19 patients, Wang et al 41 identified MEWS as an efficient tool for rapid assessment and the ROC analysis (AUC = 0.913) suggested that the MEWS was capable of predicting in-hospital mortality. Although MEWS has been found to be useful in elderly COVID-19 patients, 40 , 41 it has rarely been used in older adults with community-acquired pneumonia (CAP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven to be a crucial tool for early identification of patients with high risk of poor outcome. 24 , 39 , 40 In elderly COVID-19 patients, Wang et al 41 identified MEWS as an efficient tool for rapid assessment and the ROC analysis (AUC = 0.913) suggested that the MEWS was capable of predicting in-hospital mortality. Although MEWS has been found to be useful in elderly COVID-19 patients, 40 , 41 it has rarely been used in older adults with community-acquired pneumonia (CAP).…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a few studies have verified the predictive value of NEWS and MEWS for the prognosis of patients with CAP. 12,[24][25][26] Hence, this study aims to investigate the feasibility of the utilization of NEWS and MEWS in assessing and predicting the mortality and ICU admission for hospitalized older patients with CAP. With the comparison to CURB-65 and qSOFA, we hope to identify the most suitable score system for better hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Os parâmetros da escala, especificamente, incluem quatro sinais vitais básicos (temperatura, pressão arterial, frequência cardíaca) e uma ferramenta de avaliação rápida do estado de consciência, a AVPU, sigla em inglês para avaliar se o paciente está acordado, verbaliza, manifesta dor ou está irresponsivo. É um escore de fácil avaliação e aplicação por qualquer profissional de saúde e a sua utilização também permite melhor comunicação e melhora da interação enfermeiromédico (BALSHI et al, 2020).…”
Section: Discussionunclassified
“…A escala Mews fornece subsídios para avaliar quatro sinais vitais, temperatura, pressão arterial, frequência cardíaca e permite uma avaliação rápida do nível de consciência como a situação de alerta, verbalização, dor e responsividade. Considerase ainda que a utilização desse instrumento é de fácil manuseio e aplicação, permite a comunicação efetiva e padronizada e a tomada de decisão em conjunto pela equipe, além de poder ser realizado por qualquer profissional desde que treinado (Balshi et al, 2020).…”
Section: Antesunclassified